PERKEMBANGAN PENDIDIKAN DAN PERILAKU KEBERAGAMAAN PADA MASA KESULTANAN SAMBAS - Isyatul Mardiyati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
From a historical perspective, Sambas Sultanate historically had a significant contribution to the diversity of the empire and the kingdoms in the archipelago. While the educational side of this empire have also contributed to the transmission of the scientific world-Malay archipelago in the context of the development of Islamic education as a chain of intellectual authority (intellectual genealogy) which in turn result in the intensification of the Islamization of Islamic civilization in Indonesia. One role of the educational Sambas Sultanate is their success in producing the best sons of the Malay world and the Islamic world, such as Indra Crown Prince, Ahmad Khatib Sambas and H. M. Basyuni Imran. To find out more about the historical development of science Sambas Sultanate both from within and outside the palace will be presented further in this paper.